Evolution and research trends of paradiplomacy. A bibliometric analysis (2023)
This research article offers a bibliometric analysis of paradiplomacy. The analysis addresses three dimensions. The first characterizes the context of scientific publications on the subject: number of publications, types of documents published, language, and countries of origin of the documents. The second is the impact of these publications: repre-sentative authors, concentration of citations by authors, and relevant journals. The third, regarding content, identifies recurrent and emerging issues on paradiplomacy research. A quantitative methodology is used with statistical mecha-nisms and collection of information in Scopus from 1984 to 2021. It is concluded, among other issues, that, although paradiplomacy is at a time of development and research consolidation, efforts should be made to consolidate specialized media to disseminate articles and to establish networks among paradiplomacy researchers.Keywords: paradiplomacy, bibliometric analysis, subnational actors, international relations.